(untitled) (Journal of the Bangladesh Agricultural University, 2014)
A total of 110 rice varieties of which 108 local (From Bangladesh Rice Research Institute) and two hybrid varieties (From ACI Ltd. Bangladesh) were used to identify the morphological traits during July, 2008 to June, 2009. These varieties represented four types viz. T. Aman (n=92), B. Aman (n=15), Boro (n=2) and Jhum accession (n=1) as described by Bangladesh Rice Research Institutes literature. Though all these materials were varied ecotypically but grown in one (T. Aman) season. Irrespective of groups of all, 90 varieties were appeared distinctly morphologically from others due to seed colour; stigma colour; anthocyanin colouration of leaf sheath, nodes and lemma:palea, presence of awn and nodal root. Among 90 distinct varieties 19 were distinctly different from others by four traits, nine by three traits, 24 by two traits and 38 varieties by only single trait. The rest 20 varieties were distinguished flag leaf: attitude of the leaf blade. This was done to assess the quality traits of distinctness as major concern and was noninfluenced by the environment. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21236 J. Bangladesh Agril. Univ. 12(1): 29-36, June 2014